PENGARUH KUALITAS PELAYANAN, PROMOSI, DAN KEPERCAYAAN TERHADAP MINAT BELI ULANG (Studi Kasus pada pengguna E-commerce Shopee Mahasiswa Universitas Islam Malang) - Nur Islamiyah; Nur Hidayati; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT            E-commerce provides great business opportunities such as product sales and online service provision and revenue growth for companies such as retailers primarily because of their easy and interactive nature, lower costs. This study aims to examine the extent of the influence of service quality, promotion, trust in Shopee users' repurchase interest. The population used in this study is S1 Students of Islamic University of Malang who are still active. After collecting data, the questionnaire will be tested for validity and reliability of the questionnaire first, then the quantitative descriptive data analysis is performed. From the results of this study the following results were obtained: (1) simultaneously service quality, promotion, and trust had a positive and significant effect on repurchase interest. (2) partially, service quality influences repurchase intention. (3) partially promotion influences repurchase intention (4) partially trust influences repurchase intention. Among the three variables that affect the repurchase interest of Shopee users of Malang Islamic University students, namely service quality, promotion and trust, there is the most dominant variable influencing repurchase interest, namely the promotion variable.Keywords: Service Quality, Promotion and Trust